Trigogebra

Geometry Level 3

{ 1 sin α sin α = m 3 1 cos α cos α = n 3 \cases{ \dfrac{1}{\sin α} - \sin α & = m^3 \\\\ \dfrac{1}{\cos α} - \cos α & = n^3 }

If real α \alpha satisfies the system of equations above, find m 2 n 2 ( m 2 + n 2 ) m^2 n^2 (m^2 + n^2) .


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Sathvik Acharya
Jan 25, 2021

m 3 = 1 sin α sin α = 1 sin 2 α sin α = cos 2 α sin α (1) m^3=\frac{1}{\sin \alpha}-\sin \alpha=\frac{1-\sin^2\alpha}{\sin \alpha}=\frac{\cos^2\alpha}{\sin \alpha} \tag{1} n 3 = 1 cos α cos α = 1 cos 2 α cos α = sin 2 α cos α (2) n^3=\frac{1}{\cos \alpha}-\cos \alpha=\frac{1-\cos^2\alpha}{\cos \alpha}=\frac{\sin^2\alpha}{\cos \alpha}\tag{2} Multiplying ( 1 ) (1) and ( 2 ) (2) , m 3 n 3 = cos 2 α sin α sin 2 α cos α = sin α cos α m^3n^3=\frac{\cos^2\alpha}{\sin \alpha} \cdot \frac{\sin^2\alpha}{\cos \alpha}=\sin \alpha \cos\alpha m 2 = sin α cos α m n 3 , n 2 = sin α cos α m 3 n \implies m^2=\frac{\sin\alpha \cos\alpha}{mn^3}\;,\;\;\;n^2=\frac{\sin \alpha \cos \alpha}{m^3n} Dividing ( 1 ) (1) and ( 2 ) (2) , m 3 n 3 = cos 2 α sin α cos α sin 2 α = cos 3 α sin 3 α \frac{m^3}{n^3}=\frac{\cos^2\alpha}{\sin \alpha}\cdot \frac{\cos\alpha}{\sin^2 \alpha} =\frac{\cos^3\alpha}{\sin^3\alpha} m n = cos α sin α \implies \frac{m}{n}=\frac{\cos\alpha}{\sin\alpha} Therefore, m 2 n 2 ( m 2 + n 2 ) = m 2 n 2 ( sin α cos α m n 3 + sin α cos α m 3 n ) = m n sin α cos α + n m sin α cos α = cos α sin α sin α cos α + sin α cos α sin α cos α = cos 2 α + sin 2 α = 1 \begin{aligned} m^2n^2(m^2+n^2)&=m^2n^2\left(\frac{\sin\alpha \cos\alpha}{mn^3}+\frac{\sin \alpha \cos \alpha}{m^3n}\right) \\ \\ &=\frac{m}{n}\sin\alpha\cos\alpha+\frac{n}{m}\sin\alpha\cos\alpha \\ \\ &=\frac{\cos\alpha}{\sin\alpha}\cdot\sin\alpha\cos\alpha+\frac{\sin\alpha}{\cos\alpha}\cdot \sin\alpha\cos\alpha \\ \\ &=\cos^2\alpha+\sin^2\alpha \\ \\ &=\boxed{1} \end{aligned}

Chew-Seong Cheong
Jan 26, 2021

m 3 = 1 sin α sin α = 1 sin 2 α sin α = cos 2 α sin α n 3 = 1 cos α cos α = 1 cos 2 α cos α = sin 2 α cos α m 3 n 3 = cos 2 α sin α sin 2 α cos α = sin α cos α m 3 n 3 = cos 2 α sin α cos α sin 2 α = cos 3 α sin 3 α m n = cos α sin α m 2 n 2 ( m 2 + n 2 ) = m 4 n 2 + m 2 n 4 = m 3 n 3 m n + m 3 n 3 n m = sin α cos α cos α sin α + sin α cos α sin α cos α = cos 2 α + sin 2 α = 1 \begin{aligned} m^3 & = \frac 1{\sin \alpha} - \sin \alpha = \frac {1-\sin^2 \alpha}{\sin \alpha} = \frac {\cos^2 \alpha}{\sin \alpha} \\ n^3 & = \frac 1{\cos \alpha} - \cos \alpha = \frac {1-\cos^2 \alpha}{\cos \alpha} = \frac {\sin^2 \alpha}{\cos \alpha} \\ \implies m^3n^3 & = \frac {\cos^2 \alpha}{\sin \alpha} \cdot \frac {\sin^2 \alpha}{\cos \alpha} = \sin \alpha \cos \alpha \\ \frac {m^3}{n^3} & = \frac {\cos^2 \alpha}{\sin \alpha} \cdot \frac {\cos \alpha}{\sin^2 \alpha} = \frac {\cos^3 \alpha}{\sin ^3 \alpha} \\ \implies \frac mn & = \frac {\cos \alpha}{\sin \alpha} \\ m^2n^2(m^2+n^2) & = m^4n^2 + m^2n^4 \\ & = m^3n^3 \cdot \frac mn + m^3n^3 \cdot \frac nm \\ & = \sin \alpha \cos \alpha \cdot \frac {\cos \alpha}{\sin \alpha} + \sin \alpha \cos \alpha \cdot \frac {\sin \alpha}{\cos \alpha} \\ & = \cos^2 \alpha + \sin^2 \alpha \\ & = \boxed 1 \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...